Omega-3 Levels in Prenatal Supplements - Scourboutakos, Mary J.; Harper, Elenee H.; Kopec, Michael T.; Rose, Lauren; Forte, Milena (American Journal of Perinatology, 2024)
Objective This study aimed to systematically document the reported omega-3 levels in commercially available prenatal supplements in the United States and Canada, and compare these levels to recommended intakes in pregnancy.Study Design Commercial prenatal supplements were identified using the Dietary Supplement Label Database (n = 50) and the Licensed Natural Health Products Database (n = 18). Mean omega-3 levels and the proportion of products meeting recommendations for pregnant women were tabulated.Results Average omega-3 levels were 368 ± 33 mg in the United States and 404 ± 72 mg in Canada. Seventy percent of products in the United States and 61% in Canada contained the amount of omega-3 levels recommended for pregnant women with sufficient intakes. Sixteen percent of products in the United States and 28% in Canada contained the dose recommended for pregnant women with insufficient intakes.Conclusion These results illustrate that commercial prenatal supplements contain a wide variety of omega-3 fatty acid levels that may or may not be consistent with recommended intake levels.Key Points
Keywords: prenatal supplements; omega-3 fatty acids; preterm birth